نحو إطار مقترح لتطبيق ميزانية البرامج والأداء لترشيد نفقات الجماعات المحلية -دراسة حالة بلدية مقرة- - • زريق نوالدين, • مخلوف سالم (جامعة المسيلة, 2022)
the program and performance budget to the budget of a municipality based in The Mesila state during the period: 2017-2020. It has come up with a proposed framework to rationalize local expenditures for 2023 by resorting to the adoption of this type of budget by local communities, which would make a qualitative leap in the conduct of local finances, particularly in maintaining the optimal exploitation of local financial resources. Keywords: Balancing programs and performance, rationalizing expenses